Pharmacokinetics, bioavailability and plasma protein binding of tolfenamic acid in rainbow trout (Oncorhynchus mykiss) - Corum, Orhan; Durna Corum, Duygu; Marin, Pedro; Acar, Omer Faruk; Aksoy, Mert; Uney, Kamil (Wiley, 2024)
AbstractBackgroundAlthough research on the mechanism and control of pain and inflammation in fish has increased in recent years, the use of analgesic drugs is limited due to the lack of pharmacological information about analgesic drugs. Tolfenamic acid is a non‐steroidal anti‐inflammatory drug and can be used in fish due to its low side effect profile and superior pharmacokinetic properties.ObjectivesThe pharmacokinetics, bioavailability and plasma protein binding of tolfenamic acid were investigated following single intravascular (IV), intramuscular (IM) and oral administration of 2 mg/kg in rainbow trout at 13 ± 0.5°C.MethodsThe experiment was carried out on a total of 234 rainbow trout (Oncorhynchus mykiss). Tolfenamic acid was administered to fish via IV, IM and oral route at a dose of 2 mg/kg. Blood samples were taken at 13 different sampling times until the 72 h after drug administration. The plasma concentrations of tolfenamic acid were quantified using high pressure liquid chromatography–ultraviolet (UV) and pharmacokinetic parameters were assessed using non‐compartmental analysis.ResultsThe elimination half‐life (t1/2ʎz) of tolfenamic acid for IV, IM and oral routes was 3.47, 6.75 and 9.19 h, respectively. For the IV route, the volume of distribution at a steady state and total body clearance of tolfenamic acid were 0.09 L/kg and 0.03 L/h/kg, respectively. The peak plasma concentration and bioavailability for IM and oral administration were 8.82 and 1.24 µg/mL, and 78.45% and 21.48%, respectively. The mean plasma protein binding ratio of tolfenamic acid in rainbow trout was 99.48% and was not concentration dependent.ConclusionsWhile IM route, which exhibits both the high plasma concentration and bioavailability, can be used in rainbow trout, oral route is not recommended due to low plasma concentration and bioavailability. However, there is a need to demonstrate the pharmacodynamic activity of tolfenamic acid in rainbow trout.
Keywords: plasma protein binding; Veterinary medicine; Anti-Inflammatory Agents, Non-Steroidal; Biological Availability; Administration, Oral; OTHER; Blood Proteins; tolfenamic acid; rainbow trout; Injections, Intramuscular; Oncorhynchus mykiss; SF600-1100; Injections, Intravenous; Animals; ortho-Aminobenzoates; bioavailability; pharmacokinetics; Protein Binding; Half-Life; 14. Life underwater